The Influence of Customer Purchase Behavior and Trust on Corporate Sustainability Dimension of Tokopedia Brand Reputation in South Cikarang - Anis, Anis; Setyaningrum, Retno Purwani (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
The rapid development of e-commerce in Indonesia has changed people's shopping behavior from conventional to digital, which has an impact on aspects of corporate sustainability, including brand reputation. Tokopedia as one of the leading e-commerce platforms, needs to understand the factors that influence the sustainability of its company, especially in terms of consumer purchasing behavior (Customer Purchase Behavior) and customer trust (Trust). The purpose of this study is to analyze the Influence of Customer Purchase Behavior and Trust on the Corporate Sustainability Dimensions of Tokopedia's Brand Reputation in South Cikarang. This study uses quantitative methods, The population in this study was Tokopedia e-commerce users, totaling 134 people. The sample used was a saturated sample, namely using the entire population as a sample of 134 respondents. Data processing used the SmartPLS version 3.0 analysis tool. The results of the analysis obtained were reputation Tokopedia in South Cikarang. Trust does not have a positive effect on Tokopedia's brand reputation in South Cikarang. Customer purchasing behavior does not have a positive effect on corporate sustainability through the mediation of Tokopedia's brand reputation in South Cikarang. Trust does not have a positive effect on corporate sustainability through the mediation of Tokopedia's brand reputation in South Cikarang.